2023
DOI: 10.1186/s40246-023-00453-z
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven identification and classification of nonlinear aging patterns reveals the landscape of associations between DNA methylation and aging

Abstract: Background Aging affects the incidence of diseases such as cancer and dementia, so the development of biomarkers for aging is an important research topic in medical science. While such biomarkers have been mainly identified based on the assumption of a linear relationship between phenotypic parameters, including molecular markers, and chronological age, numerous nonlinear changes between markers and aging have been identified. However, the overall landscape of the patterns in nonlinear changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Okada et al (68) have employed mutual information to craft a DNA methylation aging clock, gauging the correlation between DNA methylation patterns and age and offering a means to estimate an individual's biological age.…”
Section: Mutual Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Okada et al (68) have employed mutual information to craft a DNA methylation aging clock, gauging the correlation between DNA methylation patterns and age and offering a means to estimate an individual's biological age.…”
Section: Mutual Informationmentioning
confidence: 99%
“…The surge in nonlinear methods for GRN reconstruction is driven by the abundance of available data (19,30,68,(133)(134)(135), offers a versatile framework. This nonlinear description enables the synthesis of diverse findings in the literature (32, 51, 57, 58).…”
Section: Modeling Nonlinear Phenomenamentioning
confidence: 99%
“…Previous works have suggested that the relationship between methylation state and age is nonlinear 14,28,[38][39][40][41] . Therefore, we decided to stratify our training data into three age groups and train separate predictors for "young", "middle-aged", and "old" subjects.…”
Section: A New Epigenetic Clock Compatible With the Epicv2 Arraymentioning
confidence: 99%
“…Previous works have suggested that the relationship between methylation state and age is nonlinear 14,28,[38][39][40][41] . Therefore, we decided to stratify our training data into three age groups and train separate predictors for "young", "middle-aged", and "old" subjects.…”
Section: A New Epigenetic Clock Compatible With the Epicv2 Arraymentioning
confidence: 99%